La idea de España en la Institución Libre de Enseñanza. Análisis de los primeros cinco años del Boletín (1877-1882) - José R. de Arellano (Cahiers de Civilisation Espagnole Contemporaine)
From its foundation in 1876 until its prohibition in 1940, the Institución Libre de Enseñanza [«Free Institution of Education»] played a central role in what we now call the Silver Age of Spanish science and culture and in the shaping of the Spanish left through tendencies like republicanism, regenerationism and socialism. The ILE’s contribution to the development of a country in great need of an educational impetus contrasts with the criticisms of anti-patriotism or Black Legend that it still receives today (Krausist philosophy, uncritical adoption of «Europeanness» as a model, etc.). It is therefore worth asking what vision of Spain and Europe can be extracted from the early texts of the ILE. By means of a lexicometric discourse analysis of the first five years of publication of its well-known Boletín and by reading some of its most significant articles, we will see that this vision is not that of Ortega y Gasset’s lapidary statement «Spain is the problem, Europe is the solution».